The role of p38-Mapk14/11 as an enabler of primitive endoderm (PrE) maturation and as a sensor of metabolism during mouse preimplantation embryo development - Thamodaran, Vasanth (Jihočeská univerzita, 2016)
ANNOTATION This thesis describes the role of p38 mitogen activated kinases alpha/beta, also referred to as Mapk14/11 (p38-Mapk14/11), in regulating primitive endoderm (PrE) cell-fate and its sensitivity towards exogenously supplemented amino acids during mouse preimplantation embryo development. This study utilizing various pharmacological inhibitors, gene transcript over-expression and immunofluorescence assisted confocal microscopy imaging, has revealed a novel and pivotal role p38-Mapk14/11 in promoting germane maturation of the blastocyst stage inner cell mass (ICM)into the defined epiblast (EPI) and PrE and its potential requirement under amino acid deprived conditions.
The role of p38-Mapk14/11 as an enabler of primitive endoderm (PrE) maturation and as a sensor of metabolism during mouse preimplantation embryo development
p38 (Mapk14/11) occupies a regulatory node governing entry into primitive endoderm differentiation during preimplantation mouse embryo development